Reduction of NOx with NH3 over Mn/TiO2 catalysts: a systematic review of the literature (Research, Society and Development, 2022)
This systematic literature review article provides an overview of results on the efficiency of supported Mn/TiO2 catalysts containing transition metals for use in the selective catalytic reduction (SCR) of NOx with NH3. The Methodi Ordinatio systematic literature methodology was applied to rank the best articles on the topic, prioritizing the journal impact factor, the year of publication and the number of citations of the scientific article. The ordering of the data showed values of NOx reduction efficiencies of up to 97% for catalysts without doping and up to 100% for materials doped with nickel, which among the related doping metals showed the best efficiency in reducing NOx with NH3. Many works related to this theme are observed and it is verified in the systematic context that materials based on manganese oxide and titanium oxide doped with transition metals or rare earth are extremely promising and efficient in the SCR-NOx with NH3.